Supercritical extrusion liquid crystal fiber reinforced PET (Polyethylene Terephthalate) foam and preparation process thereof
Through the preparation process of supercritical extruded liquid crystal fiber reinforced PET foam, the self-reinforcement characteristics of liquid crystal fibers and the crystallization induction effect of nucleating agents are used to solve the problem of insufficient PET foam performance, and high strength, high modulus and excellent machinery are achieved Performance of PET foam preparation reduces the risk of failure of additive reactions.
Patent Information
- Application Number
- CN202411428307.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-14
- Publication Date
- 2024-12-27
AI Technical Summary
Existing PET foams are difficult to meet the performance requirements of high strength and high modulus, and traditional fiber-reinforced polymer materials have shortcomings in performance improvement and cost control.
The preparation process of supercritical extruded liquid crystal fiber reinforced PET foam is used, and the PET is granulated and blended with liquid crystal materials, chain extenders, nucleating agents and antioxidants to perform supercritical extrusion foaming, and liquid crystal fibers are used. The self-enhanced properties and crystallization induction of nucleating agents form high-strength and high-modulus PET foam.
The high strength, high modulus and excellent mechanical properties of PET foam are achieved, which reduces the use of traditional fiber reinforced materials, improves the crystallization performance and cell stability of the material, and avoids the mixing of additives during foaming. Unevenness and reaction failure problems.
Smart Images

Figure BDA0005082825400000021 
Figure BDA0005082825400000071 
Figure BDA0005082825400000081
Abstract
Description
Technical Field
[0001] The invention belongs to the field of polymer material preparation, and in particular relates to a supercritical extruded liquid crystal fiber reinforced PET foam and a preparation process thereof. Background Art
[0002] As the market's requirements for product performance continue to increase, the requirements for PET foam performance are becoming more and more stringent. It is usually difficult for a single PET foam to meet these various requirements. In order to obtain PET foam with excellent performance, in addition to continuously developing new materials, multi-phase materials formed by the combination of two or more materials, namely composite PET foam, came into being. By taking advantage of the strengths and weaknesses of the original components, it forms a more reasonable composition, and thus has excellent properties that single-phase materials do not have. In recent years, resin-based composite materials have attracted much attention due to their excellent appearance, outstanding properties and low cost. Among them, fiber-reinforced polymer materials have been valued by the engineering community for their superior performance. Research on the preparation and performance improvement methods of fiber-reinforced polymers, and then developing fiber-reinforced polymers with superior performance, has important theoretical significance and engineering value. Summary of the invention
[0003] In view of the above-mentioned deficiencies of the prior art, the present invention solves the problem of providing a supercritical extruded liquid crystal fiber reinforced PET foam with higher strength and modulus and a preparation process thereof.
[0004] To solve the above problems, the technical solution adopted by the present invention is as follows:
[0005] A preparation process of supercritical extrusion liquid crystal fiber reinforced PET foam, the steps are as follows:
[0006] S1. Material drying: Put the PET and liquid crystal materials into a vacuum drying oven and dry them;
[0007] S2, liquid crystal spinning: melt spinning the liquid crystal polymer to obtain liquid crystal fibers;
[0008] S3, material granulation: the chain extender, nucleating agent, antioxidant, and liquid crystal fiber are respectively blended and granulated with PET through an extruder, and each particle is crystallized and dried after granulation to obtain a chain extender masterbatch, a nucleating agent masterbatch, an antioxidant masterbatch, and a liquid crystal fiber masterbatch;
[0009] S4, extrusion foaming: adding each mixed particle in step S3 into an extruder for extrusion foaming to obtain supercritical extruded liquid crystal fiber reinforced PET foam.
[0010] Furthermore, in step S1, the drying temperature is 120° C. and the drying time is 4 hours.
[0011] Furthermore, in step S1, the PET is bottle-grade PET; the liquid crystal material is a type III liquid crystal material having the following structural formula:
[0012]
[0013] Furthermore, in step S3, the concentrations of chain extender, nucleating agent, antioxidant and liquid crystal fiber are 15%, 30%, 10% and 30%.
[0014] Furthermore, in step S3, the granulation process is twin-screw side-feeding extrusion granulation, water cooling and air cooling and drying, and cantilever pelletizing.
[0015] Furthermore, in step S3, the chain extender is pyromellitic anhydride chain extender; the nucleating agent is a composite nucleating agent of organic phosphate and talcum powder; and the antioxidant is a hindered phenol antioxidant.
[0016] Furthermore, in step S3, the weight proportions of the components are: 77-84 parts of PET, 3-10 parts of liquid crystal fiber masterbatch, 7-9 parts of chain extender masterbatch, 5-6 parts of nucleating agent masterbatch, and 1-2 parts of antioxidant masterbatch.
[0017] Furthermore, in step S4, the foaming process is supercritical extrusion foaming, and the supercritical fluid is CO2.
[0018] A PET foam is prepared by a preparation process of supercritical extrusion liquid crystal fiber reinforced PET foam.
[0019] The beneficial effects of the present invention are as follows:
[0020] 1. The macromolecular chains of the liquid crystal polymer used in the present invention are different from the macromolecular structures of conventional polymers, which are tortuous, random coils and mutually networked. Liquid crystal polymers are composed of rigid macromolecules without mutually networked structures. Under melt molding conditions, the viscosity drops sharply and the rigid macromolecules are very easy to be highly oriented in the direction of melt flow and arranged in one direction. After cooling and solidification, this macromolecular arrangement is maintained to form highly oriented rod-shaped macromolecules. This macromolecular structure composed of aromatic polyester basic chains has high strength, high modulus and excellent mechanical properties. This rigid rod-shaped structure has the characteristics of spontaneous orientation. When melt-processed, the molecules are further oriented along the flow direction under the action of shear stress to reach a highly ordered state. After cooling, this orientation is fixed and thus has the characteristics of self-reinforcement. Even without adding reinforcing materials, the mechanical strength of ordinary engineering plastics reinforced with tens of percent glass fiber can be achieved or even exceeded, showing the characteristics of high strength and high modulus. After blending with PET, foaming LCP is prone to significantly improve the properties of the PET continuous phase, which is conducive to the generation of shear slip bands and microcracks under stress, relaxes the stress concentration at the crack end, and hinders the expansion of cracks. Secondly, liquid crystal compounds have the important characteristics of self-reinforcement and easy orientation. Under the action of external force field, they are easy to form particles and microfiber molecular chain orientation to produce some microfiber structures, so that the mixed foaming material has the shape and properties similar to fiber-reinforced materials, and obtain fiber-reinforced PET foam with high strength and high modulus.
[0021] 2. Traditional chain extenders, antioxidants and other auxiliary raw materials are powdered. If they are directly mixed with plastic particles and added to the extruder for foaming, it is easy to cause uneven mixing and clogging of the feed port. Therefore, before extrusion foaming, it is necessary to granulate the powdered auxiliary agents with PET separately, and then mix the obtained auxiliary composite particles with the resin particles before extrusion foaming.
[0022] 3. In the present invention, the antioxidant composite particles and the chain extender composite particles are mixed and granulated together during the granulation process. When the chain extender is granulated with PET particles alone, the chain extender will react with PET, causing viscosity increase and difficulty in traction granulation. In addition, if the chain extender and PET particles react too quickly during the granulation process, they are easily ineffective in the subsequent foaming process. Therefore, the reaction rate of PET and the chain extender should be slowed down during the granulation process, or the reaction time should be reduced. When granulated together with the antioxidant, the antioxidant is a small molecule substance with a low melting point and viscosity and good fluidity after melting, which can play a lubricating role. In addition, the hydroxyl group in the hindered phenol antioxidant molecule is limited by spatial obstacles, and the hydrogen atom (H) is easily detached from the original molecular structure, thereby achieving the effect of donating protons and combining with the peroxyl free radicals (ROO-) and hydroxyl free radicals generated during the aging process of PET, causing it to lose its original activity, resulting in the termination of the aging reaction to reduce the degradation during the PET processing process and maintain the reaction functionality and quality stability of the chain extender.
[0023] 4. The liquid crystal material and PET added in the present invention are both similar in polyester group structure and have good compatibility with each other. After blending, the liquid crystal fiber in the blend acts as a nucleating agent and plays a role of a heterogeneous nucleating agent, and the crystallization induction period becomes shorter and the crystallization rate is accelerated. At the same time, the temperature corresponding to the crystallization induction period and the maximum crystallization rate is reduced. This shows that the liquid crystal fiber promotes the crystallization process of PET. Its addition, on the one hand, reduces the free energy necessary for the formation of stable crystal nuclei in the high temperature zone of PET, so that the PET macromolecular chain segments can quickly form thermodynamically stable crystal nuclei of a certain size at a higher temperature, so that the subsequent crystal nucleus growth is rapid and greatly shortened The induction period, on the other hand, provides a larger free volume for the PET chain segments to diffuse to the crystal nucleus and regularly stack, thereby reducing the diffusion activation energy of the PET chain segments when they are transported across the solid-liquid interface to the spherulite surface, and correspondingly reduces the lower temperature limit of crystal growth, thereby increasing the crystal growth rate, improving the crystallization performance, and maintaining the cell stability of the PET foam material. DETAILED DESCRIPTION
[0024] The present invention is described in further detail below.
[0025] Example 1
[0026] A preparation process of supercritical extrusion liquid crystal material reinforced PET foam, the steps are as follows:
[0027] S1. Material drying: Put PET and liquid crystal material into a vacuum drying oven and dry them at 120°C for 4 hours; PET is bottle-grade PET; liquid crystal material is type III liquid crystal material;
[0028] S2, liquid crystal spinning: melt spinning the liquid crystal polymer to obtain liquid crystal fibers;
[0029] S3, material granulation: the chain extender, nucleating agent, antioxidant, liquid crystal fiber are blended with PET through an extruder to form granules, the chain extender, nucleating agent, antioxidant, liquid crystal fiber account for 15%, 30%, 10%, 30% of PET respectively, and each particle is crystallized and dried after granulation; the chain extender masterbatch, nucleating agent masterbatch, antioxidant masterbatch, liquid crystal fiber masterbatch are obtained; the granulation process is twin-screw side feeding extrusion granulation, water cooling and air cooling drying, cantilever pelletization; the chain extender is pyromellitic anhydride chain extender; the nucleating agent is 2,2′-methylenebis(4,6-tert-butylphenol)phosphine aluminum salt (NA-21) and inorganic talc powder 1000 mesh in a ratio of 1:1; the antioxidant is a hindered phenol antioxidant;
[0030] S4, extrusion foaming: PET, liquid crystal fiber masterbatch, chain extender masterbatch, nucleating agent masterbatch, and antioxidant masterbatch are fed into a mixer for blending; the weight proportions of each component are: 84 parts of PET, 3 parts of liquid crystal fiber masterbatch, 6 parts of chain extender composite particles, 5 parts of nucleating agent masterbatch, and 2 parts of antioxidant composite particles; the mixed particles are added into an extruder for extrusion foaming to obtain liquid crystal fiber reinforced PET foam; the foaming process is supercritical extrusion foaming, and the supercritical fluid is CO2.
[0031] Example 2
[0032] A preparation process of supercritical extrusion liquid crystal fiber reinforced PET foam, the steps are as follows:
[0033] S1. Material drying: Put PET and liquid crystal material into a vacuum drying oven and dry them at 120°C for 4 hours; PET is bottle-grade PET; liquid crystal material is type III liquid crystal material;
[0034] S2, liquid crystal spinning: melt spinning the liquid crystal polymer to obtain liquid crystal fibers;
[0035] S3, material granulation: the chain extender, nucleating agent, antioxidant, liquid crystal fiber are blended with PET through an extruder to form granules, the chain extender, nucleating agent, antioxidant, liquid crystal fiber account for 15%, 30%, 10%, 30% of PET respectively, and each particle is crystallized and dried after granulation; the chain extender masterbatch, nucleating agent masterbatch, antioxidant masterbatch, liquid crystal fiber masterbatch are obtained; the granulation process is twin-screw side feeding extrusion granulation, water cooling and air cooling drying, cantilever pelletization; the chain extender is pyromellitic anhydride chain extender; the nucleating agent is 2,2′-methylenebis(4,6-tert-butylphenol)phosphine aluminum salt (NA-21) and inorganic talc powder 1000 mesh in a ratio of 1:1; the antioxidant is a hindered phenol antioxidant;
[0036] S4, extrusion foaming: PET, liquid crystal fiber masterbatch, chain extender masterbatch, nucleating agent masterbatch, and antioxidant masterbatch are fed into a mixer for blending; the weight proportions of each component are: 83 parts of PET, 4 parts of liquid crystal fiber masterbatch, 6 parts of chain extender masterbatch, 5 parts of nucleating agent masterbatch, and 2 parts of antioxidant masterbatch; the mixed particles are added into an extruder for extrusion foaming to obtain liquid crystal material reinforced PET foam; the foaming process is supercritical extrusion foaming, and the supercritical fluid is CO2.
[0037] Example 3
[0038] A preparation process of supercritical extrusion liquid crystal material reinforced PET foam, the steps are as follows:
[0039] S1. Material drying: Put PET and liquid crystal materials into a vacuum drying oven and dry them at 120°C for 4 hours; PET is bottle-grade PET; liquid crystal material is type III liquid crystal material;
[0040] S2, liquid crystal spinning: melt spinning the liquid crystal polymer to obtain liquid crystal fibers;
[0041] S3, material granulation: material granulation: the chain extender, nucleating agent, antioxidant, liquid crystal fiber are respectively blended with PET through an extruder to form granules, the chain extender, nucleating agent, antioxidant, liquid crystal fiber account for 15%, 30%, 10%, 30% of PET respectively, and each particle is crystallized and dried after granulation; the chain extender masterbatch, nucleating agent masterbatch, antioxidant masterbatch, liquid crystal fiber masterbatch are obtained; the granulation process is twin-screw side feeding extrusion granulation, water cooling and air cooling drying, cantilever pelletization; the chain extender is pyromellitic anhydride chain extender; the nucleating agent is 2,2′-methylenebis(4,6-tert-butylphenol)phosphine aluminum salt (NA-21) and inorganic talc powder 1000 mesh in a ratio of 1:1; the antioxidant is a hindered phenol antioxidant;
[0042] S4, extrusion foaming: PET, liquid crystal fiber masterbatch, chain extender masterbatch, nucleating agent masterbatch, and antioxidant masterbatch are fed into a mixer for blending; the weight proportions of each component are: 82 parts of PET, 5 parts of liquid crystal fiber masterbatch, 6 parts of chain extender masterbatch, 5 parts of nucleating agent masterbatch, and 2 parts of antioxidant masterbatch; the mixed particles are added into an extruder for extrusion foaming to obtain liquid crystal material reinforced PET foam; the foaming process is supercritical extrusion foaming, and the supercritical fluid is CO2.
[0043] Example 4
[0044] A preparation process of supercritical extrusion liquid crystal material reinforced PET foam, the steps are as follows:
[0045] S1. Material drying: Put PET and liquid crystal materials into a vacuum drying oven and dry them at 120°C for 4 hours; PET is bottle-grade PET; liquid crystal material is type III liquid crystal material;
[0046] S2, liquid crystal spinning: melt spinning the liquid crystal polymer to obtain liquid crystal fibers;
[0047] S3, material granulation: material granulation: the chain extender, nucleating agent, antioxidant, liquid crystal fiber are respectively blended with PET through an extruder to form granules, the chain extender, nucleating agent, antioxidant, liquid crystal fiber account for 15%, 30%, 10%, 30% of PET respectively, and each particle is crystallized and dried after granulation; the chain extender masterbatch, nucleating agent masterbatch, antioxidant masterbatch, liquid crystal fiber masterbatch are obtained; the granulation process is twin-screw side feeding extrusion granulation, water cooling and air cooling drying, cantilever pelletization; the chain extender is pyromellitic anhydride chain extender; the nucleating agent is 2,2′-methylenebis(4,6-tert-butylphenol)phosphine aluminum salt (NA-21) and inorganic talc powder 1000 mesh in a ratio of 1:1; the antioxidant is a hindered phenol antioxidant;
[0048] S4, extrusion foaming: PET, liquid crystal fiber masterbatch, chain extender masterbatch, nucleating agent masterbatch, and antioxidant masterbatch are fed into a mixer for blending; the weight proportions of each component are: 81 parts of PET, 6 parts of liquid crystal fiber masterbatch, 6 parts of chain extender masterbatch, 5 parts of nucleating agent masterbatch, and 2 parts of antioxidant masterbatch; the mixed particles are added into an extruder for extrusion foaming to obtain liquid crystal material reinforced PET foam; the foaming process is supercritical extrusion foaming, and the supercritical fluid is CO2.
[0049] Example 5
[0050] A preparation process of supercritical extrusion liquid crystal material reinforced PET foam, the steps are as follows:
[0051] S1. Material drying: Put PET and liquid crystal materials into a vacuum drying oven and dry them at 120°C for 4 hours; PET is bottle-grade PET; liquid crystal material is type III liquid crystal material;
[0052] S2, liquid crystal spinning: melt spinning the liquid crystal polymer to obtain liquid crystal fibers;
[0053] S3, material granulation: material granulation: the chain extender, nucleating agent, antioxidant, liquid crystal fiber are respectively blended with PET through an extruder to form granules, the chain extender, nucleating agent, antioxidant, liquid crystal fiber account for 15%, 30%, 10%, 30% of PET respectively, and each particle is crystallized and dried after granulation; the chain extender masterbatch, nucleating agent masterbatch, antioxidant masterbatch, liquid crystal fiber masterbatch are obtained; the granulation process is twin-screw side feeding extrusion granulation, water cooling and air cooling drying, cantilever pelletization; the chain extender is pyromellitic anhydride chain extender; the nucleating agent is 2,2′-methylenebis(4,6-tert-butylphenol)phosphine aluminum salt (NA-21) and inorganic talc powder 1000 mesh in a ratio of 1:1; the antioxidant is a hindered phenol antioxidant;
[0054] S4, extrusion foaming: PET, liquid crystal fiber masterbatch, chain extender masterbatch, nucleating agent masterbatch, and antioxidant masterbatch are fed into a mixer for blending; the weight proportions of each component are: 80 parts of PET, 7 parts of liquid crystal fiber masterbatch, 6 parts of chain extender masterbatch, 5 parts of nucleating agent masterbatch, and 2 parts of antioxidant masterbatch; the mixed particles are added into an extruder for extrusion foaming to obtain liquid crystal material reinforced PET foam; the foaming process is supercritical extrusion foaming, and the supercritical fluid is CO2.
[0055] Example 6
[0056] A preparation process of supercritical extrusion liquid crystal material reinforced PET foam, the steps are as follows:
[0057] S1. Material drying: Put PET and liquid crystal materials into a vacuum drying oven and dry them at 120°C for 4 hours; PET is bottle-grade PET; liquid crystal material is type III liquid crystal material;
[0058] S2, liquid crystal spinning: melt spinning the liquid crystal polymer to obtain liquid crystal fibers;
[0059] S3, material granulation: material granulation: the chain extender, nucleating agent, antioxidant, liquid crystal fiber are respectively blended with PET through an extruder to form granules, the chain extender, nucleating agent, antioxidant, liquid crystal fiber account for 15%, 30%, 10%, 30% of PET respectively, and each particle is crystallized and dried after granulation; the chain extender masterbatch, nucleating agent masterbatch, antioxidant masterbatch, liquid crystal fiber masterbatch are obtained; the granulation process is twin-screw side feeding extrusion granulation, water cooling and air cooling drying, cantilever pelletization; the chain extender is pyromellitic anhydride chain extender; the nucleating agent is 2,2′-methylenebis(4,6-tert-butylphenol)phosphine aluminum salt (NA-21) and inorganic talc powder 1000 mesh in a ratio of 1:1; the antioxidant is a hindered phenol antioxidant;
[0060] S4, extrusion foaming: PET, liquid crystal fiber masterbatch, chain extender masterbatch, nucleating agent masterbatch, and antioxidant masterbatch are fed into a mixer for blending; the weight proportions of each component are: 79 parts of PET, 8 parts of liquid crystal fiber masterbatch, 6 parts of chain extender masterbatch, 5 parts of nucleating agent masterbatch, and 2 parts of antioxidant masterbatch; the mixed particles are added into an extruder for extrusion foaming to obtain liquid crystal material reinforced PET foam; the foaming process is supercritical extrusion foaming, and the supercritical fluid is CO2.
[0061] Example 7
[0062] A preparation process of supercritical extrusion liquid crystal material reinforced PET foam, the steps are as follows:
[0063] S1. Material drying: Put PET and liquid crystal materials into a vacuum drying oven and dry them at 120°C for 4 hours; PET is bottle-grade PET; liquid crystal material is type III liquid crystal material;
[0064] S2, liquid crystal spinning: melt spinning the liquid crystal polymer to obtain liquid crystal fibers;
[0065] S3, material granulation: material granulation: the chain extender, nucleating agent, antioxidant, liquid crystal fiber are respectively blended with PET through an extruder to form granules, the chain extender, nucleating agent, antioxidant, liquid crystal fiber account for 15%, 30%, 10%, 30% of PET respectively, and each particle is crystallized and dried after granulation; the chain extender masterbatch, nucleating agent masterbatch, antioxidant masterbatch, liquid crystal fiber masterbatch are obtained; the granulation process is twin-screw side feeding extrusion granulation, water cooling and air cooling drying, cantilever pelletization; the chain extender is pyromellitic anhydride chain extender; the nucleating agent is 2,2′-methylenebis(4,6-tert-butylphenol)phosphine aluminum salt (NA-21) and inorganic talc powder 1000 mesh in a ratio of 1:1; the antioxidant is a hindered phenol antioxidant;
[0066] S4, extrusion foaming: PET, liquid crystal fiber masterbatch, chain extender masterbatch, nucleating agent masterbatch, and antioxidant masterbatch are fed into a mixer for blending; the weight proportions of each component are: 78 parts of PET, 9 parts of liquid crystal fiber masterbatch, 6 parts of chain extender masterbatch, 5 parts of nucleating agent masterbatch, and 2 parts of antioxidant masterbatch; the mixed particles are added into an extruder for extrusion foaming to obtain liquid crystal material reinforced PET foam; the foaming process is supercritical extrusion foaming, and the supercritical fluid is CO2.
[0067] Example 8
[0068] A preparation process of supercritical extrusion liquid crystal material reinforced PET foam, the steps are as follows:
[0069] S1. Material drying: Put PET and liquid crystal materials into a vacuum drying oven and dry them at 120°C for 4 hours; PET is bottle-grade PET; liquid crystal material is type III liquid crystal material;
[0070] S2, liquid crystal spinning: melt spinning the liquid crystal polymer to obtain liquid crystal fibers;
[0071] S3, material granulation: material granulation: the chain extender, nucleating agent, antioxidant, liquid crystal fiber are respectively blended with PET through an extruder to form granules, the chain extender, nucleating agent, antioxidant, liquid crystal fiber account for 15%, 30%, 10%, 30% of PET respectively, and each particle is crystallized and dried after granulation; the chain extender masterbatch, nucleating agent masterbatch, antioxidant masterbatch, liquid crystal fiber masterbatch are obtained; the granulation process is twin-screw side feeding extrusion granulation, water cooling and air cooling drying, cantilever pelletization; the chain extender is pyromellitic anhydride chain extender; the nucleating agent is 2,2′-methylenebis(4,6-tert-butylphenol)phosphine aluminum salt (NA-21) and inorganic talc powder 1000 mesh in a ratio of 1:1; the antioxidant is a hindered phenol antioxidant;
[0072] S4, extrusion foaming: PET, liquid crystal fiber masterbatch, chain extender masterbatch, nucleating agent masterbatch, and antioxidant masterbatch are sent into a mixer for blending; the weight parts of each component are: PET 77 parts, liquid crystal fiber masterbatch 10 parts, chain extender masterbatch 6 parts, nucleating agent masterbatch 5 parts, and antioxidant masterbatch 2 parts. The mixed particles are added into an extruder for extrusion foaming to obtain liquid crystal material reinforced PET foam; the foaming process is supercritical extrusion foaming, and the supercritical fluid is CO2.
[0073]
[0074]
[0075]
[0076] Performance test comparison
[0077] From the above table, we can see that the closed-cell rate and glue absorption amount of foaming materials with the same density have nothing to do with the amount of liquid crystal material added. As the amount of liquid crystal material added increases, the thermal conductivity of the foam increases. This is because the addition of liquid crystal materials can effectively increase the crystallization rate of PET foam and the more regular lattice structure. This structure is conducive to heat transfer because heat can be transferred through the vibration of the lattice. In terms of mechanical properties, liquid crystal materials have greatly improved the tensile and compressive properties of PET foam. This is because liquid crystal compounds have the important characteristics of self-reinforcement and easy orientation. During the extrusion and stretching process, it is easy to form particles and microfiber molecular chain orientation to produce some microfiber structures, making the mixed foaming material have an effect similar to that of fiber-reinforced materials. In addition, on the whole, the addition of liquid crystal materials will increase the crystallization performance of the material, thereby causing the toughness of PET foam to decrease and the shear strength to decrease.
[0078] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A process for preparing supercritical extruded liquid crystal fiber reinforced PET foam, characterized in that: Here are the steps: S1. Material drying: Put the PET and liquid crystal materials into a vacuum drying oven and dry them; S2, liquid crystal spinning: melt spinning the liquid crystal polymer to obtain liquid crystal fibers; S3, material granulation: the chain extender, nucleating agent, antioxidant, and liquid crystal fiber are respectively blended and granulated with PET through an extruder, and each particle is crystallized and dried after granulation to obtain a chain extender masterbatch, a nucleating agent masterbatch, an antioxidant masterbatch, and a liquid crystal fiber masterbatch; S4, extrusion foaming: adding each mixed particle in step S3 into an extruder for extrusion foaming to obtain supercritical extruded liquid crystal fiber reinforced PET foam.
2. The preparation process of supercritical extruded liquid crystal fiber reinforced PET foam according to claim 1, characterized in that: In step S1, the drying temperature is 120° C. and the drying time is 4 hours.
3. The preparation process of supercritical extruded liquid crystal fiber reinforced PET foam according to claim 1, characterized in that: In the step S1, the PET is bottle-grade PET; the liquid crystal material is a type III liquid crystal material with the following structural formula:
4. The preparation process of supercritical extruded liquid crystal fiber reinforced PET foam according to claim 1, characterized in that: In the step S3, the concentrations of the chain extender, the nucleating agent, the antioxidant, and the liquid crystal fiber are 15%, 30%, 10%, and 30%.
5. The preparation process of supercritical extruded liquid crystal fiber reinforced PET foam according to claim 1, characterized in that: In the step S3, the granulation process is twin-screw side-feeding extrusion granulation, water cooling plus air cooling and drying, and cantilever pelletizing.
6. The preparation process of supercritical extruded liquid crystal fiber reinforced PET foam according to claim 1, characterized in that: In the step S3, the chain extender is pyromellitic anhydride chain extender; the nucleating agent is a composite nucleating agent of organic phosphate and talcum powder; and the antioxidant is a hindered phenol antioxidant.
7. The process for preparing supercritical extruded liquid crystal fiber reinforced PET foam according to claim 1, characterized in that: In step S3, the weight proportions of the components are: 77-84 parts of PET, 3-10 parts of liquid crystal fiber masterbatch, 7-9 parts of chain extender masterbatch, 5-6 parts of nucleating agent masterbatch, and 1-2 parts of antioxidant masterbatch.
8. The process for preparing supercritical extruded liquid crystal fiber reinforced PET foam according to claim 1, characterized in that: In step S4, the foaming process is supercritical extrusion foaming, and the supercritical fluid is CO2.
9. A PET foam prepared according to the preparation process of supercritical extrusion liquid crystal fiber reinforced PET foam according to claim 1.
Citation Information
Cited By
High-strength and high-toughness PET foam as well as raw material composition and preparation method thereof
CN119391151A
High-strength, high-toughness pet foam, raw material composition therefor, and preparation method therefor
WO2026144224A1
